SC48 Developing a simulation-based education workshop for psychiatric emergencies for national roll-out. (3rd November 2019) - Creed, Michael; Bhulbh, Áine de; O'Connor, Diarmuid; McMahon, Eimear; Doherty, Anne; Byrne, Dara
Abstract : Background: The use of simulation-based education in psychiatry has been increasing in recent years outside of Ireland. Its use has been demonstrated to be an effective means of training in management of acute agitation¹, and advancing communication skills amongst psychiatrists². However, adoption of simulation has been slow in psychiatry training in Ireland. A need was identified for the development of a simulation-based education workshop to improve management of psychiatric emergencies, for trainees new to psychiatry, such as Foundation Year trainees and GP trainees. Summary of project: Four scenarios were identified and developed using an iterative collaborative process involving a consultant psychiatrist, psychiatry trainees, psychiatry nurses and simulation staff. The scenarios were: the difficult discharge of a patient; completing an involuntary admission under the Mental Health Act, 2001; management of an acutely agitated patient in the Emergency Department; and risk assessment of a suicidal young man. The scenarios were scripted and actors were trained as simulated persons, and a detailed dry run took place in advance of the workshop. Workshop participants ranged from Foundation Year trainees to Higher Specialist Trainees. Debriefing was led by consultant psychiatrists and the actors. Post workshop satisfaction surveys were circulated and semi-structured reflective interviews were conducted after 3–4 weeks to examine impact on clinical practice. Summary of results: Post evaluation data (n=12) was positive with 100% agreeing that the workshop addressed their learning needs. Participants highlighted the benefits of reflection with consultant feedback after each scenario, and an improvement in communication skills. Participants also enjoyed the social aspect of the workshop, and more senior trainees found it a beneficial refresher of basic skills. All wanted further training with suggestions for other scenarios including psychiatry-specific medical emergencies, and assessment of emergency presentations of children and adolescents. Delayed interviews (n=5) showed that participants had applied their learning to their practice in the domains of situational awareness and communication. A handbook was developed following the workshop, detailing the scenarios and including all paperwork relevant to the scenarios, for implementation in other training sites. Discussion, conclusions and recommendations: Simulation-based education is a suitable method of training for psychiatric emergencies. The design of a workshop requires detailed scenario development and training of actors in playing simulated persons. There is scope for a roll-out of simulation-based education in post-graduate psychiatry training nationally, supported by the handbook developed from this workshop. References: Vestal HS, Sowden G, Nejad S, Stoklosa J, Valcourt SC, Keary C, Caminis A, Huffman J. Simulation-Based Training for Residents in the Management of Acute Agitation: A Cluster Randomized Controlled Trial. Acad Psychiatry . 2017 Feb; 41(1): 62–67. Brenner A. Uses and limitations of simulated patients in psychiatric education. Acad Psychiatry . 2009; 33: 112–119.